Blended Finance as a Solution for SDG Financing: Global Voices in Scientific Literature (2010–2025) - Judijanto, Loso; Haryadi, Haryadi (West Science Social and Humanities Studies, 2025)
This study examines the global progression of blended finance as a mechanism for financing Sustainable Development Goals (SDGs) via bibliometric and content analysis of publications from 2010 to 2025. The research employs Scopus-indexed data and analytical tools, including VOSviewer and Biblioshiny, to delineate publication trends, topic clusters, and collaborative networks across many fields and locations. The findings identify three primary study clusters: (1) the mobilization of private capital via concessional mechanisms, (2) governance, transparency, and additionality in development finance, and (3) sectoral applications in climate, infrastructure, and MSME development. The United Kingdom, Malaysia, and the United States excel in academic production and inter-institutional cooperation, although rising economies like Indonesia and India are enhancing their research prominence. Notwithstanding conceptual advancement, the study reveals enduring deficiencies in empirical validation and fair implementation in least developed countries (LDCs). The work advances theory by framing blended finance as a hybrid mechanism that amalgamates public-private governance with sustainable investment principles. It underscores the necessity for transparency, impact assessment, and inclusive design to guarantee catalytic and equitable results.